Produced Water Treatment Using Ultrafiltration and Nanofiltration Membranes - Sherhan, Bashir Y.; Abbas, Areej D.; Alsalhy, Qusay F.; Rashad, Alaa A.; Rashad, Zahraa W.; Shawkat, Aiden A.; Abbas, Thamera K.; Mahdi, yusra M.; Abdul Kareem, Noura A. (Al-Khwarizmi Engineering Journal, 2017)
The application of ultrafiltration (UF) and nanofiltration (NF) processes in the handling of raw produced water have been investigated in the present study. Experiments of both ultrafiltration and nanofiltration processes are performed in a laboratory unit, which is operated in a cross-flow pattern. Various types of hollow fiber membranes were utilized in this study such as poly vinyl chloride (PVC) UF membrane, two different polyether sulfone (PES) NF membranes, and poly phenyl sulfone PPSU NF membrane. It was found that the turbidity of the treated water is higher than 95 % by using UF and NF membranes. The chemical oxygen demand COD (160 mg/l) and Oil content (26.8 mg/l) were found after treatment according to the allowable limits set by means of world health organization WHO water quality standards. The final composition of SO4-2 (110 mg/l) and NO3 (48.4 mg/l) components within the produced water after treatment were agreed with the permissible limits of WHO, whereas Cl-1 (8900 mg/l) component is not in the allowable limits. Finally by the use of PVC, PES and PPSU hollow fiber membranes; this method is seen to be not sufficient to remove the salinity of the produced water.